Library as Laboratory: Computer Science Students Practice Usability Engineering in an Academic Library. - Margaret Mellinger (Issues in Science and Technology Librarianship, 2007)
This article presents a project-based collaboration between a usability engineering (UE) course and the campus library. Student teams developed UE projects based on usability issues they identified in the library's web-based and information technology services. Using the library as a focal point, students practiced common UE methods such as ethnomethodological observation, web usability evaluation, and an iterative prototype process based on cycles of design, testing and evaluation. At the end of the term, teams of students presented their novel solutions to library staff as part of their final grade. Other academic librarians may find inspiration to pursue similar partnerships on their own campuses.